THE RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION AND THE INCIDENCE OF DIARRHEA IN TODDLERS IN HAMLET III RUGEMUK VILLAGE, LABU BEACH, DELI SERDANG - Nanda, Meutia; Safira, Putri; Salsabilla, Salsabilla; Sibuea, Alya Az Zahra; Anggraini, Riri (HEARTY, 2024)
Environmental sanitation is an important factor in the prevention of diseases, including diarrhea in toddlers. Hamlet III of Rugemuk Village in Deli Serdang has sanitation challenges that can affect public health. The purpose of the study was to determine the relationship between environmental sanitation and the incidence of diarrhea in toddlers in Hamlet III Rugemuk Village, Labu Beach, Deli Serdang. This study is a quantitative study with a cross sectional design, the population of this study is all mothers who have toddlers as many as 107 people. The sampling technique uses simple random sampling with representatives of mothers who have 51 toddlers . This study was analyzed by univariate and bivariate analysis using the chi-square test. The instrument used was a questionnaire. The results of the study found that there was no statistically significant relationship between the type of clean water facilities and the incidence of diarrhea (p-value = 1.103), there was a statistically significant relationship between the condition of family toilet facilities and the incidence of diarrhea (p-value = 0.047), there was a relationship between the condition of eligible waste disposal facilities and the incidence of diarrhea (p-value = 0.006), there was a relationship between the condition of wastewater disposal facilities and incidence of diarrhea (p-value = 0.001). Thus, it can be concluded that family latrines, garbage disposal facilities, and wastewater disposal facilities have a significant relationship with the incidence of diarrhea, while the relationship with clean water facilities is not statistically significant. In an effort to improve environmental sanitation, it is important for the surrounding community to improve family latrines, manage qualified waste and wastewater and carry out effective counseling.